PERMAINAN TRADISIONAL SONDOK-SONDOK-AN DI DESA MUARO SENTAJO KABUPATEN KUANTAN SINGINGI - ", Asmarilli; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Game of sondok-sondok-an is traditional game of society go abroad Kuantan precisely traditional game of country of Sentajo. Game of sondok-sondok-an much the same to with game of petak umpet. So that game of this sondok-sondok-an is progressively enthused and do not be forgotten by children of ought to redefined traditional game to children so that them know any kind of traditional game exist in its area each. This research aim to to know social system elements and perception of old fellow to traditional game of sondok-sondok-an. Research location in Countryside of Muaro Sentajo District Sentajo Raya Sub-Province Kuantan Singingi. Analysis date in this research is analysis of desriptif qualitative. Result of research is social system elements at traditional game of sondok-sondok-an which consist of from 10 element that is knowledge or confidence, feeling, target of and target, norm, role and status, rank and level, influence or power, sanction, tension pressure and medium. the social system The tenth can at game of sondok-sondok-an. Perception of old fellow to game of sondok-sondok-an very good, where old fellow perception of game give influence which good to children if seen from way of game of sondok-sondok-an, role which is played in game of sondok-sondok-an, benefit game of sondok-sondok-an, and values exist in game of sondok-sondok-an so that the continuity of permianan of sondok-sondok-an require to be fought for by all side.